Dynamical model of an obscuring clumpy torus in AGNs – I. Velocity and velocity dispersion maps for interpretation of ALMA observations. Issue 1 (18th February 2021) - Bannikova, E Yu; Sergeyev, A V; Akerman, N A; Berczik, P P; Ishchenko, M V; Capaccioli, M; Akhmetov, V S
ABSTRACT: We have developed the dynamical model of a clumpy torus in an active galactic nucleus (AGN) and compared to recent The Atacama Large Millimeter Array (ALMA) observations. We present N -body simulations of a torus in the field of a supermassive black hole (SMBH), made of up to N = 10 5 gravitationally interacting clouds. As initial conditions, we choose random distributions of the orbital elements of the clouds with a cut-off in the inclination to mimic the presence of wind cones produced at the early AGN stage. When the torus reaches an equilibrium, it has a doughnut shape. We discuss the presence of box orbits. We have then constructed the velocity and velocity dispersion maps using the resulting distributions of the clouds at equilibrium. The effects of torus inclination and cloud sizes are duly analysed. We discuss the obscuration effects of the clouds using a ray tracing simulation matching the model maps to ALMA resolution. By comparing the model with the observational maps of NGC 1068, we find that the SMBH mass is M_smbh=5× 10^6 M_ for the range of the torus inclination angles 45°–60°. We also construct the velocity dispersion maps for NGC 1326 and NGC 1672. They show that the peaks in the ALMA dispersion maps are related to the emission of the torus throat. Finally, we obtain the temperature distribution maps with parameters that correspond to our model velocity maps for NGC 1068. They show stratification in temperature distribution with the shape of the high-temperature region as in the VLTI/MIDI map.